Does unfairness hurt women? - Piasenti, Stefano,Valente, Marica,Veldhuizen, Roel van,Pfeifer, Gregor (IZA - Institute of Labor Economics, 2023)
How do men and women differ in their persistence after experiencing failure in a competitive environment? We tackle this question by combining a large online experiment (N=2,086) with machine learning. We find that when losing is unequivocally due to merit, both men and women exhibit a significant decrease in subsequent tournament entry. However, when the prior tournament is unfair, i.e., a loss is no longer necessarily based on merit, women are more discouraged than men. These results suggest that transparent meritocratic criteria may play a key role in preventing women from falling behind after experiencing a loss.
10419/279022
Keywords: Graue Literatur; competitiveness; gender; fairness; machine learning; online experiment